2004
DOI: 10.1002/tox.20048
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on sensitivity of higher plants and fish to heavy fuel oil

Abstract: Laboratory tests were conducted on higher plants [garden cress (Lepidium sativum), great duckweed (Spirodela polyrrhiza), and Tradescantia clone BNL 02] and fish [rainbow trout (Oncorhynchus mykiss) at all stages of development: eggs, larvae and adults] to estimate their sensitivity to heavy fuel oil (HFO). A number of biological indices (survival, growth, and physiological and morphological parameters) as well as the genotoxic impact (Tradescantia) of HFO was evaluated by acute and chronic toxicity tests. Fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…It can be concluded that sensitivity of L. sativum and S. polyrrhiza to the impact of substances present in tannery waste water differs. Previous investigations have demonstrated, that L. sativum is more sensitive to organic substances (Kazlauskienė et al, 2004), while S. polyrrhiza is more sensitive to the impact of heavy metals ).…”
Section: Tannerymentioning
confidence: 94%
See 1 more Smart Citation
“…It can be concluded that sensitivity of L. sativum and S. polyrrhiza to the impact of substances present in tannery waste water differs. Previous investigations have demonstrated, that L. sativum is more sensitive to organic substances (Kazlauskienė et al, 2004), while S. polyrrhiza is more sensitive to the impact of heavy metals ).…”
Section: Tannerymentioning
confidence: 94%
“…Bioassays estimate the combined effects of all components present (Wang et al, 2001;Blinova, 2004;Montvydienė and Marčiulionienė, 2004;Loureiro et al, 2006). A bioassays battery is widely used to assess the potential adverse effects of existing or new chemical substances and to evaluate the impact of these substances on various spheres of ecosystems in which they may get into (79/831/EEC, Johnson et al, 2004;Kazlauskienė et al, 2004). Usually it is recommended that species representing different trophic levels be included in the battery (Johnson et al, 2004;Selivanovskaya and Latypova, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…polyrrhiza, which is the largest duckweed (giant duckweed) in the Lemnaceae family, is frequently used to determine the potential impacts of heavy metals and other pollutants in environmental risk assessments. It is a sensitive plant that could exhibit effects when treated in low concentrations [22,23]. Herein, we used it to evaluate the bleaching activities of the title compounds (Table 1).…”
Section: Herbicidal Activitymentioning
confidence: 99%
“…Toksikologiniams tyrimams dažniausiai pasirenkamos žuvys, kadangi jos yra geriausiai ištyrinėti vandens organizmai, be to, daugybė tyrimų rodo, kad žuvys ankstyvuoju vystymosi laikotarpiu yra labai jautrios teršalams Svecevičius et al 2003;Kazlauskienė et al 2004;Vosylienė et al 2005).…”
Section: įVadasunclassified
“…Kadangi natūraliomis sąlygomis gyvus organizmus beveik visada veikia ne viena, bet iš karto kelios medžiagos, todėl gamtiniuose vandenyse esantys metalų mišiniai gali sumažinti žuvų išgyvenimą esant ankstyvajai ontogenezei, sutrikdyti jų vystymąsi ir išsiritimą, kurie savo ruožtu gali turėti neigiamų pasekmių žuvų vėlesnių kartų kokybei ir visai populiacijai (Kazlauskienė et al 2004;Jezierska et al 2009). …”
Section: Eksperimentinio Tyrimo Rezultatai Ir Jų Analizėunclassified